Impacts of climate change on wine grape farming in the Western Cape: Implications for adaptation - Slater, Shane (Department of Environmental and Geographical Science, 2024)
Research indicates that climate change can be expected to result in a warming and drying effect in the Western Cape's most highly productive wine grape growing regions by the 2040s. This could pose serious challenges to the yield and quality of wine grapes produced in the region, as it negatively affects the Mediterranean-like conditions that are desirable for wine grape production. Farmers will need to address this issue by exploring adaptation methods to lessen the impacts of climate change. The research sought to integrate farmer perceptions of climate change with scientific literature on adaptation, in order to suggest the most feasible adaptation strategies for 10 sample wine farms. This is expected to contribute an understanding of the vulnerability of wine farmers to climate change and find ways to increase their adaptive capacity. Analysis of weather trends from weather station data indicate that the Western Cape seems to be heading towards a generally warmer climate, therefore affecting the ability to produce quality wine grapes, particularly white grapes which are less heat-tolerant. The research found that although wine farmers are aware of weather patterns, climate and its impacts on viticulture, their willingness to engage in adaptive strategies differed. Particularly, those who had already experienced severe negative impacts on wine production ( as a result of extreme weather) were more willing to currently explore adaptation options.